2017
DOI: 10.1016/j.regsciurbeco.2017.04.006
|View full text |Cite
|
Sign up to set email alerts
|

The effect of direct democracy on the level and structure of local taxes

Abstract: Die Dis cus si on Pape rs die nen einer mög lichst schnel len Ver brei tung von neue ren For schungs arbei ten des ZEW. Die Bei trä ge lie gen in allei ni ger Ver ant wor tung der Auto ren und stel len nicht not wen di ger wei se die Mei nung des ZEW dar.Dis cus si on Papers are inten ded to make results of ZEW research prompt ly avai la ble to other eco no mists in order to encou ra ge dis cus si on and sug gesti ons for revi si ons. The aut hors are sole ly respon si ble for the con tents which do not neces … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…The availability of a pre-and post-treatment period together with population size dependent thresholds allows us to combine RD and difference-in-differences methods and to implement a difference-in-discontinuities (diff-in-disc) design (e.g., Grembi et al, 2014;Casas-Arce and Saiz, 2015). 3 Related studies that use the same natural experiment but study different questions are Arnold and Freier (2015), who explore how signature requirements affect direct democratic activity, and Asatryan et al (2014), who study the effect of direct democracy on the level and structure of local taxes. Asatryan and De Witte (2015) also exploit the Bavarian direct democracy reforms, but study its effects on government efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…The availability of a pre-and post-treatment period together with population size dependent thresholds allows us to combine RD and difference-in-differences methods and to implement a difference-in-discontinuities (diff-in-disc) design (e.g., Grembi et al, 2014;Casas-Arce and Saiz, 2015). 3 Related studies that use the same natural experiment but study different questions are Arnold and Freier (2015), who explore how signature requirements affect direct democratic activity, and Asatryan et al (2014), who study the effect of direct democracy on the level and structure of local taxes. Asatryan and De Witte (2015) also exploit the Bavarian direct democracy reforms, but study its effects on government efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…At the institutional level, local authorities will become fully dependent on local domestic and business property taxes rather than transfers, and this may shift the relative influence of local voters and business owners. For example, Asatryan et al (2017) found in Germany that business taxes rather than personal taxes rose in response to improvements in local democracy. In the UK, this may be particularly interesting, given the much greater reliance on property taxes than in other OECD countries.…”
Section: Discussionmentioning
confidence: 99%
“…That was the result of the regionalization of the people who were ordered to follow instructions from superiors. Originally as a traditional leader, the village head had strong ties and commitment to the village community (Asatryan, Baskaran, & Heinemann, 2017).…”
Section: Introductionmentioning
confidence: 99%